2017
DOI: 10.1002/ep.12701
|View full text |Cite
|
Sign up to set email alerts
|

Kallar grass (Leptochloa fusca L. Kunth) as a feedstock for ethanol fermentation with the aid of response surface methodology

Abstract: In this study, Leptochloa fusca L. Kunth or Kallar grass (KG) was thermochemically (0.625M NaOH solution followed by steam treatment at 121°C for 1 h) pretreated and utilized as a substrate for ethanol production in simultaneous saccharification and fermentation process. A four‐factor, full factorial, rotatable central composite design of response surface methodology was used to develop a statistical model for the optimization of process variables such as substrate concentration, enzyme concentration, temperat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 27 publications
1
4
0
Order By: Relevance
“…process's main objective is to decrease the degree of polymerization of cellulose by hydrolyzing the large polysaccharides to simple sugar yeast to produce bioethanol [28]. The graph in Figure 7 is in line with the previous study by Gul et al, where the highest concentration of bioethanol from Kallar grass by Kluyveromyces marxianus was obtained at 32 h fermentation time, and the concentration tends to decrease [29]. This result indicates that bamboo can produce bioethanol optimally after the combination of MW pretreatment and hydrolysis by cellulase enzyme were done.…”
Section: Effect Of Mw Pretreatment On Ssfsupporting
confidence: 88%
“…process's main objective is to decrease the degree of polymerization of cellulose by hydrolyzing the large polysaccharides to simple sugar yeast to produce bioethanol [28]. The graph in Figure 7 is in line with the previous study by Gul et al, where the highest concentration of bioethanol from Kallar grass by Kluyveromyces marxianus was obtained at 32 h fermentation time, and the concentration tends to decrease [29]. This result indicates that bamboo can produce bioethanol optimally after the combination of MW pretreatment and hydrolysis by cellulase enzyme were done.…”
Section: Effect Of Mw Pretreatment On Ssfsupporting
confidence: 88%
“…In this context, bioethanol from lignocellulosic biomass (LCB) is considered to be one of the important promising alternative liquid fuels [2]. The use of lignocellulosic biomass as feedstock for bioethanol production [3] has certain advantages over the fossil fuels. LCB has a high potential for ethanol production, they are abundant renewable resources, has a variety of source, do not compete with the first generation of biofuel, and could integrate as Integrated Biomass Utilization System (IBUS) [4].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, hydrolysis time showed the greatest impact on the sugar concentrations, and it was observed that longer hydrolysis time resulted in higher sugar concentrations for both enzymes (Figure 2b and 2c). Similarly, Gul et al (2018) showed that longer hydrolysis time caused higher saccharification efficiency from Kallar grass. Furthermore, Kshirsagar et al (2015) found the optimal conditions for reducing sugar yield from rice straw as 40 FPU/g enzyme and 17.50% biomass loading for 72 h when the researchers used RSM for the experiments.…”
Section: Response Surface Methodologymentioning
confidence: 95%